The Flexibility of Ḥadīths and the Authority of Fatwas as a Post-Covid-19 Reflection - Rahima Rahima; Yulia Rahmi; M. Iqbal Al-Rusyd (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2026)
The COVID-19 pandemic raised significant theological and legal questions concerning the implementation of congregational worship and public health measures within Muslim communities. Although ḥadīths on epidemics have long served as normative references in Islamic jurisprudence, their contemporary interpretation and practical application in religious legal opinions (fatwas) and local contexts remain insufficiently examined. This study aims to analyze the flexibility of the Prophet Muḥammad's ḥadīths on epidemics and their implementation in contemporary fatwas and Muslim religious practices in North Sumatra, Indonesia. Employing a qualitative approach with a descriptive-analytical design, the study combines thematic analysis of authentic ḥadīths, comparative analysis of institutional fatwas, and qualitative interviews with Muslim scholars in North Sumatra. The findings demonstrate that the ḥadīths articulate enduring principles of epidemic management, including regional quarantine, isolation of infected individuals, medical treatment, tawakkul (trust in God), and the spiritual merit associated with patience during epidemics. Contemporary Muslim scholars reinterpret these principles contextually while preserving their normative foundations. The North Sumatra case further reveals that differences in the implementation of fatwas are shaped by contrasting textualist and maqāṣid-oriented approaches as well as by local social and religious dynamics. This study highlights the adaptability of Islamic legal reasoning in responding to public health crises and contributes to the development of a more systematic and anticipatory framework for pandemic fiqh.